Paṇḍita Dalam Teks Agastya Parwa - Ida Bagus Subrahmaniam Saitya; A.A. Diah Indrayani (Jayapangus Press, 2020)
Agastya Parwa is an old Javanese manuscript in the form of prose and old age (Century IX-XI M). The text of Agastya Parwa is in fact closely related to the name Bhagawān Agastya as a Maha Ṛṣi Hindu who contributed to the spread of Hinduism from the Sindhu river valley to all of India, Central Asia, China, Japan and Indonesia. The text of Agastya Parwa is used as a source in yajña, this means the text belongs to the ceremonial group, but there is also a saying that this text belongs to the ethical group because this text contains the teachings of ethics, especially the doctrine of swadharma from a paṇḍita